Measuring the impact of HRM on organizational performance - Anastasia A. Katou (Journal of Industrial Engineering and Management (JIEM), 2008)
The purpose of this paper is to measure the impact of HRM on organisational performance in the context of Greece. Data were collected from 178 organisations using a questionnaire survey in the Greek manufacturing sector, and analysed using the "structural equation modelling" methodology. The results indicated that the relationship between HRM policies (resourcing and development, compensation and incentives, involvement and job design) and organisational performance is partially mediated through HRM outcomes (skills, attitudes, behaviour), and it is influenced by business strategies (cost, quality, innovation). Thus, the contribution of this study for academics and practitioners is that HRM policies associated with business strategies will affect organisational performance through HRM outcomes.
Keywords: 650; HRM policies; organisational performance; Greece